Evaluation of blood pressure in school children aged 12-16 years - Nadesan, Balakrishnan; Sachithananthamoorthi, Mani Madhavan; Thirumalaikumarasamy, Sivaraman; Ramalingam, Ezhilarasu (International Journal of Contemporary Pediatrics, 2017)
Background: Hypertension is considered as a major health issue in developed as well as developing countries and its possible origin during childhood prompts pediatricians to routinely include measurement of blood pressure (BP) as an integral part of pediatric physical examination. The objectives of the study were to evaluate the normal range of blood pressure in adolescent school going students of 12-16 years, prevalence of hypertension and relationship of BP with variables like age, body mass index (BMI), socioeconomic status and family history of hypertension. Methods: A cross sectional study was undertaken for a period of one year in adolescent school children in age groups between 12-16 years. Detailed clinical examination was done in 1060 adolescent school children and BP was recorded in right upper limb and correlation of BP with BMI, family history of hypertension and diabetes were studied. Results: Mean systolic and diastolic pressure showed linear relationship with age. There was a highly statistically significant difference between mean systolic and diastolic blood pressure between lower and middle socio-economic class. Prevalence of obesity in our study was 1.13%, overweight was 7.83%. Prevalence of hypertension in obese children was 33.33% and in overweight children 18.07%. Family history of hypertension and diabetes carry a significant correlation with elevated systolic and diastolic blood pressure in adolescents. Conclusions: This study revealed that socio economic factors play a significant role in determining the blood pressure of the individual. Children of middle class have significantly elevated mean systolic pressure and mean diastolic pressure than low socio-economic groups.